ROLE OF RISK FACTORS IN THE DEVELOPMENT OF COMPLICATIONS OF TYPE 2 DIABETES IN ADULTS - Dilafruz G. Abdullaeva ,; Feruz K. Khomidov , (Central Asian Journal of Medicine, 2024)
This article discusses the prevention of type 2 diabetes in adults. The purpose of the work is to study and implement preventive measures for the prevention of type 2 diabetes. Material and methods. Analysis of the results of the questionnaire and clinical laboratory examination. Results. There is an increase in diabetes mellitus across the world among different age groups; each country has different climatic and geographic characteristics and dietary traditions. Taking them into account, it is necessary to develop a plan of preventive measures to solve the problem.